2022
DOI: 10.3390/cancers14041025
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Plasma Cell-Free DNA and Its DNA Integrity and Hypomethylation Status as Biomarkers for Tumor Burden and Disease Progression in Patients with Metastatic Neuroendocrine Neoplasias

Abstract: Background: Neuroendocrine neoplasia (NEN) encompasses a diverse group of malignancies marked by histological heterogeneity and highly variable clinical outcomes. Apart from Chromogranin A, specific biomarkers predicting residual tumor disease, tumor burden, and disease progression in NEN are scant. Thus, there is a strong clinical need for new and minimally invasive biomarkers that allow for an evaluation of the prognosis, clinical course, and response to treatment of NEN patients, thereby helping implement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Analogously, the cfDI values of both ALU 260/111 and LINE-1 266/97 were lower in BC patients than in healthy controls in agreement with the findings of Madhavan et al [7]. Of note, all studies with ALU 260/111 or LINE-1 266/97 observed a decrease in cfDI in cancer patients versus healthy controls [7,10,19], as we previously noted [6]. On the contrary, other targets such as ALU 245/115 [15,18], ALU 247/60 [20], and LINE-1 259/97 [17] showed an increase in the cfDI of cancer patients versus healthy controls.…”
Section: Discussionsupporting
confidence: 87%
“…Analogously, the cfDI values of both ALU 260/111 and LINE-1 266/97 were lower in BC patients than in healthy controls in agreement with the findings of Madhavan et al [7]. Of note, all studies with ALU 260/111 or LINE-1 266/97 observed a decrease in cfDI in cancer patients versus healthy controls [7,10,19], as we previously noted [6]. On the contrary, other targets such as ALU 245/115 [15,18], ALU 247/60 [20], and LINE-1 259/97 [17] showed an increase in the cfDI of cancer patients versus healthy controls.…”
Section: Discussionsupporting
confidence: 87%
“…Studies in eight different cancer cell lines and patients' plasma samples have elucidated the characteristics of cfDNA, confirming its release exclusively by cancer cells, with different release patterns [211][212][213][214][215][216]. Screening of the bioenergetics flux parameters showed a correlation between cfDNA release patterns and cellular origin, cancer status, and proliferation phase [217][218][219][220]. A significant dependence correlating with cfDNA release was noted with aerobic glycolysis but not OXPHOS [219,221,222].…”
Section: Theranostic Insights In Tumor-tme-bioenergtics Interfacementioning
confidence: 80%
“…Moreover, elevated ccfDNA plasma concentrations have been reported to be associated with vascular invasions and tumor burden in various types of malignancies. [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%